Improving Rural Water Service in Rwanda with Public-Private Partnerships - Christophe Prevost; Mwanafunzi, Bruno; Jain, Nitin (World Bank, Washington, DC, 2012)
In 2004, a field review commissioned by the World Bank found that half of the piped rural water supply systems in Rwanda were nonfunctional due to poor management and poor cost recovery. In response, the government shifted to a public-private partnership (PPP) management model. As of 2010, 235 rural water supply systems, 28 percent of the 847 systems in the country, are managed under PPPs serving one million people. This smart lesson shares what the World Bank and Water and Sanitation Program (WSP) learned in support of Rwanda's remarkable progress, including using best practices to make the case for reform; fostering ownership, simplicity, and flexibility of design; using peer-to-peer learning; and evaluating factors for success.